Riding the waves of culture : understanding diversity in global business. - Trompenaars, Alfons; Hampden-Turner, Charles (McGraw-Hill, 2021)
This is the fourth edition of the definitive text on cultural diversity in business that encourages us to understand our own culture in the work place before managing or doing business with other national cultures.